The Impact of Industrial Land Dependence on Industrial Land Use Efficiency and Its Heterogeneity: A Panel Test Based on 286 Cities in China - Xinmei Yang; Ruihui Zhou (SAGE Open)
Local governments’ monopolistic low-price supply of industrial land has long induced industrial land dependence (ILD), triggering a “resource curse” that hinders high-quality industrial development. Using panel data from 286 Chinese cities (2003–2022), this study examines ILD’s impact on industrial land use efficiency (ILUE), its transmission mechanisms, and heterogeneity. Drawing on resource curse theory, we propose that ILD reduces ILUE via enterprise entry-exit imbalances, resource misallocation, innovation suppression, and environmental pollution. Innovations include: (1) Focusing on existing low-efficiency land rather than new allocations; (2) Employing mediation effect models to verify ILD’s pathways through excessive enterprise entry, hindered low-efficiency exits, rigid resource allocation, innovation suppression, and pollution exacerbation; (3) Using the 2012 abandoned industrial land reclamation pilot as a negative shock to reveal ILD’s curse mechanism. Results show: (1) ILD significantly reduces ILUE, while reclamation pilots enhance ILUE; (2) Mediation analysis confirms enterprise imbalances, resource misallocation, and innovation suppression mediate ILD’s negative effects, with pollution amplifying efficiency losses; (3) Land marketization and industrial restructuring significantly boost ILUE in small-medium and non-resource-based cities. This study offers policy insights for breaking the industrial land curse, fostering economic growth, and upgrading industrial structures. JEL Classification: R14, R52, Q24, Q32.